Stable Matching on the Job? Theory and Evidence on Internal Talent Markets - Bo Cowgill; Jonathan Davis; B. Pablo Montagnes; Patryk Perkowski (Institute of Labor Economics (IZA), 2024)
A principal often needs to match agents to perform coordinated tasks, but agents can quit or slack off if they dislike their match. We study two prevalent approaches for matching within organizations: Centralized assignment by firm leaders and self-organization through market-like mechanisms. We provide a formal model of the strengths and weaknesses of both methods under different settings, incentives, and production technologies. The model highlights tradeoffs between match-specific productivity and job satisfaction. We then measure these tradeoffs with data from a large organization's internal talent market. Firm-dictated matches are 33% more valuable than randomly assigned matches within job categories (using the firm's preferred metric of quality). By contrast, preference-based matches (using deferred acceptance) are only 5% better than random but are ranked (on average) about 38 percentiles higher by the workforce. The self-organized match is positively assortative and helps workers grow new skills; the firm's preferred match is negatively assortative and harvests existing expertise.
Keywords: M5; D47; J4; 330; internal labor markets; assortative matching; assignment mechanisms; team formation; matching